2020
DOI: 10.1002/ca.23665
|View full text |Cite
|
Sign up to set email alerts
|

A reliable septum exists between the lateral cord and medial and posterior cords in the costoclavicular region: Clinical and microanatomical considerations in brachial plexus anesthetic blockade

Abstract: Background and Objectives The ultrasound‐guided proximal infraclavicular costoclavicular block (PICB) appears popular but its results are inconsistent. We sought an accurate demonstration of septae formed between the brachial plexus cords. Methods We performed in‐plane, lateral‐to‐medial PICBs on 120 patients and recorded images. Once the most superficial lateral cord component was entered, a 0.4–0.6 mA current was applied to confirm needle placement; 5 ml of local anesthetic (LA) solution was then injected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Based on the findings in Reina’s study [ 14 ], the LA is probably deposited between the epineurium of the trunks for the DI technique, which was described as the “investing adipose layers” in Siddiqui’s study [ 5 ]. However, the epineurium is usually reinforced by a closed paraneurium layer, which acts as an important tissue barrier to obstruct the spread of LA, thus delaying its block effects; similar findings have been reported in the costoclavicular space [ 15 , 16 ]. Several studies comparing sub-epineurium vs extra-epineurium injection for brachial plexus blocks have demonstrated that deliberately penetrating the epineurium rather than the internal epineurium layer is more successful, resulting in faster onset times and higher success rates with no increased incidence in complications [ 11 , 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…Based on the findings in Reina’s study [ 14 ], the LA is probably deposited between the epineurium of the trunks for the DI technique, which was described as the “investing adipose layers” in Siddiqui’s study [ 5 ]. However, the epineurium is usually reinforced by a closed paraneurium layer, which acts as an important tissue barrier to obstruct the spread of LA, thus delaying its block effects; similar findings have been reported in the costoclavicular space [ 15 , 16 ]. Several studies comparing sub-epineurium vs extra-epineurium injection for brachial plexus blocks have demonstrated that deliberately penetrating the epineurium rather than the internal epineurium layer is more successful, resulting in faster onset times and higher success rates with no increased incidence in complications [ 11 , 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…Two patients (5.4%) in the MISB group and three patients (7.7%) in the LISB group underwent trachea intubation and general anesthesia. The reasons may be the long distance for extending, the "compartment effect" of trunks or cords separated by blood vessels or muscle slip, the septum between the lateral cord and medial and posterior cords, and additional communicating branches between the components of the brachial plexus [24][25][26][27][28][29]. Most patients in the two groups had satisfied pain relief within 12 h. However, after that, the tramadol requirement gradually increased, which was consistent with previous studies in arthroscopic shoulder surgery of ISB because ropivacaine was absorbed and metabolized gradually after 12 h followup [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…We conclude from our results that the CC approach should be favored, even at a low anesthetic volume, with the compact location of the dense plexus sheath and cords. A close examination of the CC anatomy has shown a high rate (94%) of intracompartmental septum presence in this region [15]. Layera et al showed a faster onset of the block with a double injection-CC approach compared to a single-injection one [16].…”
Section: Discussionmentioning
confidence: 99%